Uso de redes sociales y logros de aprendizaje en estudiantes de secundaria del área de desarrollo personal ciudadanía y cívica, Institución Educativa Kairós Christian School, Iquitos 2023 - Mattos Tuesta, Bruce Diago (2025)
The main purpose was to diagnose the association between the use of social networks and learning achievements in secondary education students. The research used a quantitative approach, with a specific cross-sectional correlational design. The sample unit consisted of 89 students from 1st to 5th grade of secondary school, working with a census sample due to accessibility to participants. The survey and documentary analysis were used as a technique and two instruments: a questionnaire and a transcript. The most important findings warn that with a significance of 0.0% and a Spearman's Rho of .435** it is concluded that: The use of social networks is significantly related to learning achievements, in students in Personal Development, Citizenship and Civics, Kairós Christian School Educational Institution, Iquitos 2023.